When the Masks Come Off in Canada and Guatemala: Will the Realities of Racism and Marginalization of Midwives Finally Be Addressed? - Daviss, Betty-Anne; Roberts, Tammy; Leblanc, Candace; Champet, Iris; Betchi, Bernadette; Ashawasegai, Angela; Gamez, Laura (Frontiers in Sociology, 2021)
This article addresses the effects of COVID-19 in Eastern and Northern Ontario, Canada, with a comparative glimpse at the small province of Totonicapán, Guatemala, with which Canadians have been involved in obstetric and midwifery care in particular over the last five years. With universal health care coverage since 1966 and well-integrated midwifery, Canada’s system would be considered relatively well set up to deal with a disaster like COVID-19 compared to the US and to low resource countries like Guatemala. However, the epidemic has uncovered the fact that in Ontario, Black, Indigenous and People of Color (BIPOC), as elsewhere, have been hardest hit. While COVID-19 could be an issue through which health care professionals can come together, there are signs that the medical hierarchies in many hospitals in both Ontario and Totonicapán are taking advantage of COVID-19 to increase interventive measures in childbirth and reduce midwives’ involvement in hospital, while home births are on the rise in both jurisdictions. Stories from a Jamaican Muslim woman in Ottawa, an Indigenous midwifery practice in Northern Ontario, midwives in Eastern Ontario, and the traditional midwives in Guatemala reveal similar as well as unique problems resulting from the lockdowns. While this article is not intended to constitute an exhaustive analysis of social justice and human rights issues in Canada and Guatemala, we do take this opportunity to demonstrate where COVID-19 has become a catalyst that challenges the standard narrative, exposing the old ruts and blind spots of inequality and discrimination that our hierarchies and inadequate data collection—until the epidemic—were managing to ignore. As health advocates, we see signs that this pandemic is resulting in more open debate, which we hope will last long after it is over in both our countries.